2011
DOI: 10.1590/s0103-84782011005000111
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stress related with mortality rates on broilers' preslaughter operations: a lairage time effect study

Abstract: Concerning the reduction of preslaughter death losses, high temperature and relative humidity in the tropics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
6
0
2
Order By: Relevance
“…The results of the present (1) (2) study are in accordance with Vieira et al (2011), who reported that the daily periods with temperature a >25 °C are the harsh periods for transportation, with respect to thermal comfort ranges for broiler chickens. During morning and night, the temperature was below the thermal comfort range of birds, either considering the thermal gradient between the crates and external environment.…”
Section: Resultssupporting
confidence: 91%
“…The results of the present (1) (2) study are in accordance with Vieira et al (2011), who reported that the daily periods with temperature a >25 °C are the harsh periods for transportation, with respect to thermal comfort ranges for broiler chickens. During morning and night, the temperature was below the thermal comfort range of birds, either considering the thermal gradient between the crates and external environment.…”
Section: Resultssupporting
confidence: 91%
“…Of the DOA evaluated by necropsy in the UK, 25% were attributed to preexisting flock health status, 35% to catching, loading, and transport injuries, and 40% of the DOA were linked to heat or cold stress (Ritz et al, 2005). High temperature and relative humidity in the tropics are major concerns regarding broiler survival prior to slaughtering (Vieira et al, 2011b). A significant relationship between the time of year and mortality rate was reported by Tabbaa and Alshawabkeh (2000) in Jordan.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have considered the effect of transportation duration and distance on animal welfare and resultant meat quality of broiler chickens. However, the reports are contradictory, where the majority of studies have associated long-term transportation to higher mortalities (Nijdam et al, 2004;Vecerek, Grbalova, Voslarova, Janackova, & Malena, 2006;Vieira, Silva, Barbosa Filho, Vieira, & Broom, 2011;Vieira, Silva, Barbosa Filho, Vieira, Rodrigues-Sarnighausen, et al, 2011;Warriss, Bevis, & Brown, 1990;Whiting et al, 2007), but some have indicated that short-term transportation could be more stressful to the birds (Vosmerova et al, 2010). Nijdam et al (2004) reported an increase of 6% in DOA for each additional 15 min in transportation time and an additional increase of 3% for each extra 15 min in lairage time based on transport of 1907 Dutch and German broiler flocks, and concluded that the concurrent effect of temperature and journey duration is an important determinant of DOA.…”
Section: Transport Duration and Distancementioning
confidence: 99%
“…The microclimate within the trailer is the most important factor affecting broiler welfare during transportation, as heat and cold stresses are two major contributors to both death and overall transportation stress in broilers (Hunter, Mitchell, & Carlisle, 1999;Hunter, Mitchell, & Matheu, 1997;Mitchell & Kettlewell, 2009;Mitchell, Kettlewell, Hunter, & Carlisle, 2001;Mitchell, Kettlewell, & Maxwell, 1994;Vieira, Silva, Barbosa Filho, Vieira, & Broom, 2011;Vieira, Silva, Barbosa Filho, Vieira, Rodrigues-Sarnighausen, et al, 2011;Weeks & Nicol, 2000). Post-mortem assessment of DOA birds has revealed that 40% of birds die from thermal stress due to uneven ventilation of the truck and failures in thermoregulation of birds (Kettlewell, Hoxey, & Mitchell, 2000;Mitchell & Kettlewell, 1998).…”
Section: Effect On Doamentioning
confidence: 99%